A review of MOOCs implementation in Malaysian higher education system / Naemah Abdul Wahab ... [et al.] - Abdul Wahab, Naemah; Othman, Jamal; Kadar, Rozita; Warris, Saiful Nizam (UiTM Cawangan Perlis, 2019)
Massive Open Online Courses (MOOCs) is a present technological innovation of teaching and learning in the modern higher education landscape. MOOCs have reformed the manner of instructional delivery by the educators as well as the way learners acquire their knowledge. For this reason, this study explores the definitions of MOOCs, its characteristics, benefits as well as drawbacks and MOOCs practices in Malaysia. We also look into the assessments and grading practices in MOOCs as well as factors affecting learners' readiness to MOOCs. Lastly, we discussed some suggestion and future directions for achieving a successful MOOCs implementation in higher education settings. From all the studies done in the recent years, we can perceive that Malaysia has taken the latest step in modernizing the method of instructional delivery in higher learning institutions through the implementation of MOOCs. Although at the moment, MOOCs in Malaysia uses its own mold by blending the traditional classroom setting with only 30 percent of MOOCs used as the online instructional approach, it still encourages learners to adapt with self-directed learning and exploring various ICT tools, inspires the educators to develop updated instructional skills and provide opportunity of lifelong learning experiences to diverse learners' backgrounds. These lifelong learning practices offer open and flexible education for the entire population, either formally or informally. Recently, Malaysian MOOCs are seen progressing towards providing professional development and training courses in future that goes beyond the need of higher education and university students.